The last mile [compact disc, unabridged] - Baldacci, David (Baldacci, David. Amos Decker series., 2016)
A new thriller featuring detective Amos Decker. Convicted murderer Melvin Mars is counting down the last hours before his execution--for the violent killing of his parents twenty years earlier--when he's granted an unexpected reprieve. Another man has confessed to the crime.